Search 74,936 tutors
FIND TUTORS
Ask a question
0 0

Factoring polynomial

Tutors, please sign in to answer this question.

2 Answers

x- 9x- x+ 9 = 0

= x4(x2-9) - (x2-9)  factor out x4 in the first two terms and a (-1) in the last two terms.                    

= (x4-1)(x2-9)       collect like terms. Ex. a(x2-c) - b(x2-c) = (a-b)(x2-c)

=(x2+1)(x2-1)(x+3)(x-3)       Difference of Two Squares: (a2-b2) = (a-b)(a+b).     x= (x2)2, so x2= a                     (x2-9) = (x-3)(x+3)    (x4-1) = (x2+1)(x2-1)

=(x2+1)(x+1)(x-1)(x+3)(x-3)        Difference of Two squares again for (x2-1) = (x+1)(x-1)